The Role of Subtitled Videos in Enhancing Intensive Listening Comprehension and Learning Motivation - Ilham, Ilham (Journal of Foreign Language Teaching and Learning, 2026)
Background: Despite the growth of multimedia in EFL, the role of subtitles in intensive listening, which demands high precision and rapid processing, is underexplored. This study addresses that gap by examining the dual impact of subtitles on both comprehension and motivation. Objective: This study aimed to investigate EFL students’ perceptions of the use of subtitled videos in relation to intensive listening comprehension and their motivation to engage in listening practice. Methods: The study employed a descriptive qualitative design at an English Education Department in Indonesia, involving 75 undergraduate students. Data were collected through a structured questionnaire and semi-structured interviews to obtain both quantitative and qualitative insights. Questionnaire data were analyzed using descriptive statistics, and interview data were analyzed using thematic analysis to identify recurring patterns in students’ perceptions. Findings: Subtitles were perceived as clear and appropriately timed, supporting learners’ comprehension of main ideas, detailed information, and the speaker's intent. Subtitles also helped students recognize new vocabulary, retain important information, and follow the flow of speech more effectively. Beyond cognitive support, subtitles enhanced learners’ focus, comfort, and confidence during listening tasks. Importantly, subtitles also fostered motivation, with students reporting increased enthusiasm, satisfaction, and consistency in practicing listening both inside and outside the classroom. Conclusion: Subtitled videos enhance both comprehension and motivation for intensive EFL listening. This dual cognitive and affective impact underscores their pedagogical value and suggests they should be integrated into multimedia listening instruction.